(untitled) (Conferencea, 2023)
A new phase transformation model is developed based on the basics of theorems about martensite phase transformation in solid materials. It is able to reflect the influences of phase transformation peak temperatures as well as the phase transformation start temperature and the phase transformation finish temperature, which overcomes the limitation that the previous phase transformation models can not reflect the influences of the phase transformation peak temperatures on the phase transformation behaviors of a NiTi alloy. Numerical examples illustrate the capability of the new phase transformation model. The thermo-mechanical behaviors of NiTi alloy are investigated through monotonic tensile tests. The multi-cycle mechanical behaviors and material training effects of NiTi alloy are investigated through multi-cycle tensile tests. A new phase transformation model with a material training effect is supposed to describe the multi-cycle phase transformation behaviors of NiTi alloy.